3D network-like porous MnCo2O4 by the sucrose-assisted combustion method for high-performance supercapacitors. Issue 2 (1st February 2017) - Huang, Tianfu; Zhao, Chenhao; Wu, Linhua; Lang, Xiaoling; Liu, Kaiyu; Hu, Zhibiao
Abstract: 3D network-like porous MnCo2 O4 nanostructures have been successfully fabricated through a facile and scalable sucrose-assisted combustion route followed by calcination treatment. Benefiting from its advantages of the unique 3D network-like architectures with large specific surface area (216.15 m 2  g −1 ), abundant mesoporosity (2–50 nm) and high electronic conductivity, the as-prepared MnCo2 O4 electrode displays a high specific capacitance of 647.42 F g −1 at a current density of 1 A g −1, remarkable capacitance retention rate of 70.67% at current density of 10 A g −1 compared with 1 A g −1, and excellent cycle stability (only 6.32% loss after 3000 cycles). The excellent electrochemical performances coupled with facile and cost effective method will render the as-fabricated 3D network-like porous MnCo2 O4 as a promising electrode material for supercapacitors.